Using a Sledgehammer to Crack a Nut? Kenya’s Approach to the Detention of Asylum Seekers and Refugees in Prisons and Police Stations - Iradukunda, Marie (Strathmore Law Review, 2024)
Article 19 of the International Covenant on Civil and Political Rights (ICCPR) provides that every person has the right to liberty and security of person. This right extends to asylum seekers and refugees and requires that they are not subjected to arbitrary detention such as detention that is disproportionate. In Kenya, the detention of asylum seekers and refugees is guided by Section 2 of the Refugees Act and Sections 4 and 12(3)(g) of the Persons Deprived of Liberty Act. These provisions provide for the administrative detention of asylum seekers and refugees in carceral institutions such as prisons and police stations. Using doctrinal analysis and qualitative research, this paper argues that this detention approach, which pursues administrative detention of asylum seekers and refugees through carceral facilities, is disproportionate. This is because the detriment to the right to liberty of asylum seekers and refugees outweighs the administrative benefits to be achieved by such detention. By being disproportionate, this approach contravenes Kenya’s international obligations under the ICCPR. To resolve this, this paper recommends the adoption of a detention approach that is more likely to be proportionate by eliminating the use of carceral institutions in the detention of asylum seekers and refugees.